Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Direct and Indirect Speech
DOI: 10.1515/9783110871968.311
|View full text |Cite
|
Sign up to set email alerts
|

Introducing constructed dialogue in Greek and American conversational and literary narrative

Abstract: The most frequent introducers are forms of the verb "say" (Greek leo). Some typical examples: English conversation: Well I went because my-my regular dentist said, "You should have your wisdom teeth taken out." American novel: "Doesn't he look handsome?" Hinda said. (p.84) Greek conversation: Tau leo "En taxei tha'rtho ti Triti to vrady." (I say to him "Okay I'll come Tuesday evening.") Greek novel: De me noiazei, elega. (It doesn't bother me, I said.) (p.73)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
168
0
16

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(197 citation statements)
references
References 16 publications
8
168
0
16
Order By: Relevance
“…As noted by , there is a tradition of sociolinguistically informed work documenting the existence of variation in narrative styles across (researcher-determined) groups, often defined by nationality, class, race/ethnicity, and/or region Mintz 1996, Miller et al 1997;Tannen 1984Tannen , 1986. Some of this scholarship involves intergroup comparisons.…”
Section: Group-specific Narrative Styles and "Cultural Identities"mentioning
confidence: 99%
“…As noted by , there is a tradition of sociolinguistically informed work documenting the existence of variation in narrative styles across (researcher-determined) groups, often defined by nationality, class, race/ethnicity, and/or region Mintz 1996, Miller et al 1997;Tannen 1984Tannen , 1986. Some of this scholarship involves intergroup comparisons.…”
Section: Group-specific Narrative Styles and "Cultural Identities"mentioning
confidence: 99%
“…While early work on reported speech and prior text largely focuses on the role of repetition and attribution, later studies, including Tannen's (1986Tannen's ( , 2007 when speech uttered in one context is repeated in another, it is fundamentally changed even if 'reported' accurately. In many, perhaps most, cases, however, material represented as dialogue was never spoken by anyone else in a form resembling that constructed, if at all.…”
Section: Reported Speech and Sharing Of Prior Textmentioning
confidence: 99%
“…While early work on reported speech and prior text largely focuses on the role of repetition and attribution, later studies, including Tannen's (1986Tannen's ( , 2007 research on constructed dialogue and Johnstone et al's (1994) research on intertextual repetition, have focused on the ways that so-called reported speech is altered when imported into new interactional environments in spoken language. Tannen (2007: 112) argues that: when speech uttered in one context is repeated in another, it is fundamentally changed even if 'reported' accurately.…”
Section: Reported Speech and Sharing Of Prior Textmentioning
confidence: 99%
“…* Four instance of <thing was> occurred in the Rankin novels; one occurred in dialog and the other three occurred in free indirect speech, which is "constructed dialogue" according to Tannen 1986and "heteroglossic" according to Bakhtin 1981[1953, both cited in Johnstone 2008: 60. These are primarily from personal blogs and represent a very informal and highly involved style which include lots of contractions and elisions, as well as being minimally edited.…”
Section: Register Distribution Of Ts Variantsmentioning
confidence: 99%